Antibacterial and Mode of Action of Extracts from Endophytic Fungi Derived from Terminalia mantaly, Terminalia catappa, and Cananga odorata - Mbekou, Michele Ines Kanko (Biomed Res Int, 2021)
Emerging drug-resistant bacteria creates an urgent need to search for antibiotics drugs with novel mechanisms of action. Endophytes have established a reputation as a source of structurally novel secondary metabolites with a wide range of biological activities. In the present study, we explore the antibacterial potential of endophytic fungi isolated from different tissues of Terminalia mantaly, Terminalia catappa, and Cananga odorata. The crude ethyl acetate extracts of 56 different endophytic fungi were screened against seven bacterial strains using the broth microdilution method. The antibacterial modes of action of the most active extracts (04) were evaluated using E. coli ATCC 25922 and H. influenzae ATCC 49247 strains. Both the DPPH and FRAP assays were used to investigate their antioxidant activity, and their cytotoxicity against the Vero cell line was evaluated using the MTT assay. Out of the 56 crude extracts tested, about 13% were considered very active, 66% partially active, and 21% nonactive against all tested bacterial strains with MIC values ranging from 0.32 μg/mL to 25 μg/mL. The four more potent extracts (MIC <5 μg/mL) (from Aspergillus sp. N454, Aspergillus sp. N13, Curvularia sp. N101, and Aspergillus sp. N18) significantly lysed the bacteria cells, increased outer membrane permeability, reduced salt tolerance, and inhibited bacterial catalase activity. They exhibited a DPPH free radical scavenging activity with IC(50) ranging from 150.71 to 936.08 μg/mL. Three of the four potent extracts were noncytotoxic against the Vero cells line (CC(50) > 100 μg/mL). Results from this investigation demonstrated that endophytes from Cameroonian medicinal plants might content potent antibacterial metabolites. The bioguided fractionation of these potent extracts is ongoing to isolate and characterise potential active ingredients.